Umbilical Cord Blood-Derived Exosomes From Very Preterm Infants With Bronchopulmonary Dysplasia Impaired Endothelial Angiogenesis: Roles of Exosomal MicroRNAs - Zhong, Xin-qi; Yan, Qin; Chen, Zhuang-gui; Jia, Chun-hong; Li, Xiu-hong; Liang, Zi-yan; Gu, Jian; Wei, Hui-ling; Lian, Chang-yu; Zheng, Jing; Cui, Qi-liang (Frontiers in Cell and Developmental Biology, 2021)
Premature infants have a high risk of bronchopulmonary dysplasia (BPD) characterized by abnormal development of alveoli and pulmonary vessel. Exosomes and exosomal miRNAs (EXO-miRNAs) from bronchoalveolar lavage fluid were shown to be involved in the development of BPD and might serve as predictive biomarkers. However, the roles of exosomes and EXO-miRNAs derived from umbilical cord blood in the incidence of BPD are yet to be elucidated. In this study, we showed that umbilical cord blood-derived exosomes in BPD group impaired angiogenesis. Next generation sequencing of the exosome RNAs uncovered a total of 418 differentially expressed EXO-miRNAs that were largely enriched in pathways including PI3K/Akt signaling pathway and angiogenesis related signaling pathways. The expression of hsa-miR-103a-3p and hsa-miR-185-5p showed the most significant reduction and hsa-miR-200a-3p was the only miRNA showing increased expression. In addition, we also found that overexpression of hsa-miR-185-5p and hsa-miR-103a-3p in HUVECs significantly enhanced endothelial cell proliferation, tube formation and cell migration; however, overexpressing hsa-miR-200a-3p gave opposite results. Our study demonstrates that exosomes derived from umbilical cord blood of BPD infants could impair angiogenesis, which is potentially mediated by differentially expressed EXO-miRNAs packaged in the exosomes.